A zero-dimensional bismuth-based perovskite structure luminescent material and preparation method thereof
By adjusting the ratio of Tb3+ and Eu3+ in bismuth-based perovskite materials and using DMSO solvents, the stability and environmental pollution problems of traditional lead-based perovskite materials are solved, and high-performance zero-dimensional bismuth-based perovskites are achieved. The preparation of structural luminescent materials is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202211143213.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-09-20
AI Technical Summary
Traditional lead-based perovskite materials have problems with toxicity, poor stability and environmental pollution, and the emission intensity of doped materials is easily affected by a variety of factors, which limits their application.
BiX6, a zero-dimensional bismuth-based perovskite structure luminescent material (TbxEu1-x·8DMSO) is used to adjust the ratio of Tb3+ and Eu3+ to achieve color conversion at different UV lamp wavelengths, and DMSO is used as the coordination ions of europium and terbium. The solvent was synthesized by cooling crystallization.
It has achieved high purity, stable fluorescence performance, strong fluorescence intensity and good color resolution. It is suitable for color displays and information anti-counterfeiting fields, and the preparation method is simple and economical, suitable for large-scale production.
Smart Images

Figure HDA0003854322250000011 
Figure HDA0003854322250000012 
Figure HDA0003854322250000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to a zero-dimensional bismuth-based perovskite structure luminescent material and a preparation method thereof. Background Art
[0002] With the improvement of social civilization, science and technology have steadily advanced, and mankind has begun to enter the intelligent information age. As a medium for information transmission, display technology plays an extremely important role in contemporary times. High-performance display devices usually have extremely strict requirements on luminescent materials. Perovskite materials have attracted much attention from researchers due to their extremely excellent optoelectronic properties and low production costs. Low-dimensional metal halide perovskites have attracted widespread attention as single-component luminescent materials, but most studies have focused on lead-based hybrid perovskites. Lead-based perovskite materials contain toxic lead ions and have high sensitivity to high temperature, humidity and oxygen, poor stability and other disadvantages, which greatly limit their service life and large-scale application, and also cause great pollution to the environment.
[0003] In recent years, rare earth fluorescent materials have attracted the interest of many people due to their fluorescent properties such as high brightness, long life, sharp emission peak and excellent luminous efficiency, and have been successfully applied in many fields. At the same time, metal halide perovskites have developed rapidly due to their high photoluminescence quantum yield (PLQY), good charge transport ability and excellent color purity. Europium ions and terbium ions are often used in the doping of metal halide perovskites due to their excellent optical properties. As doping materials, they can enhance the luminescence of perovskite materials to a certain extent. However, doping materials are mostly doped at the B position, and their emission intensity is easily affected by conventional factors such as dopant-matrix combination, particle size, phase, shape, temperature, electric field, solvent, etc. Therefore, there is still a lot of research space for the application of rare earth fluorescent materials in perovskite materials. Summary of the invention
[0004] The present invention provides a zero-dimensional bismuth-based perovskite structure luminescent material (Tb x Eu 1-x ·8DMSO)BiX6 and its preparation method. The luminescent material has high purity, stable fluorescence performance, high fluorescence intensity, good color resolution, and exhibits good visible adjustable luminescence characteristics. It can emit light of different colors under ultraviolet lamps with different excitation wavelengths. It has broad application prospects in the fields of color displays, fluorescent lamps, and information anti-counterfeiting. The preparation method is simple and conducive to promotion.
[0005] To achieve the above object, the technical solution of the present invention is:
[0006] Provided is a zero-dimensional bismuth-based perovskite structure luminescent material having a structural formula of (Tb x Eu 1-x·8DMSO)BiX6, where 0≤x≤1, X is Cl - Br - ,I - One or more of .
[0007] According to the above scheme, the zero-dimensional bismuth-based perovskite structure luminescent material is adjusted by 3+ and Eu 3+ The ratio of green light to yellow light and then to red light is achieved under the irradiation of ultraviolet light with a wavelength of 350-400nm.
[0008] According to the above scheme, when europium ions and terbium ions exist at the same time, preferably 0.8≤x≤0.4, more preferably 0.8≤x≤0.6, it is possible to emit light of different colors under ultraviolet lamps with different excitation wavelengths; among which orange-yellow light is emitted under ultraviolet lamps at 350-370nm, typically 365nm, and red light is emitted at a wavelength of 380-400nm, typically 395nm.
[0009] A method for preparing the above-mentioned zero-dimensional bismuth-based perovskite structure light-emitting material is provided, comprising the following steps:
[0010] 1) weighing a soluble salt of terbium, a soluble salt of europium and a bismuth source in sequence according to the calculated ratio of the structure, adding them to a dimethyl sulfoxide solution, and then heating and stirring;
[0011] 2) After stirring in step 1) until the mixture is clear and transparent, the mixture is cooled and crystallized, and then post-treated to obtain a zero-dimensional bismuth-based perovskite structured luminescent material.
[0012] According to the above scheme, in step 1), the soluble salt of terbium is one or more of hydrochloride, nitrate, carbonate and acetate.
[0013] According to the above scheme, in step 1), the soluble salt of europium is one or more of hydrochloride, nitrate, carbonate and acetate.
[0014] According to the above scheme, in step 1), the bismuth source is one or more of bismuth chloride, bismuth bromide, and bismuth iodide.
[0015] According to the above scheme, in step 1), the heating and stirring conditions are: heating to 65°C-95°C, and the stirring time is 0.5-2.5 hours.
[0016] According to the above scheme, in step 2), the programmed cooling conditions are: cooling by 2-8°C per hour for 16-30 hours.
[0017] According to the above scheme, in step 2), the post-treatment is: filtering the crystals, then washing them with isopropanol or anhydrous ethanol for 2-3 times, and drying them.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention provides a zero-dimensional bismuth-based perovskite-structured luminescent material. Different from the traditional perovskite in which the A-site ion is a single inorganic metal ion or a single organic ligand, the luminescent material uses a large-size complex ion formed by the coordination of rare earth ions and solvents as the A-site ion to obtain a perovskite-like structure, whose luminescence center is a rare earth ion, and the emission spectrum is mainly dominated by rare earth ion emission. The fluorescence performance is more stable, the fluorescence intensity is higher, and the color resolution is better. At the same time, it also provides a new design idea for the development of perovskite structure.
[0020] 2. The luminescent material of the present invention can be adjusted by Tb 3+ and Eu 3+ The ratio of Tb can realize the color change under the same wavelength of ultraviolet light. At the same time, the color resolution of the present invention is high under ultraviolet light, which is conducive to the naked eye to change Tb 3+ and Eu 3+ By adjusting the concentration of the coordinated ions, the material exhibits good visible tunable luminescence properties and has broad application prospects in color displays and fluorescent lamps.
[0021] 3. In the luminescent material of the present invention, when europium ions and terbium ions exist at the same time, different colors of light can be emitted under ultraviolet lamps with different excitation wavelengths; for example, orange-yellow light is emitted under ultraviolet lamps at a wavelength of 350-370nm, such as 365nm, and red light is emitted under a wavelength of 380-400nm, such as 395nm. The fluorescent quantum yield is high, the color brightness is high, the color difference is obvious, and it is easy to observe with the naked eye, so it has broad development prospects in anti-counterfeiting applications.
[0022] 4. The present invention provides a method for preparing a zero-dimensional bismuth-based perovskite-structured luminescent material, which uses a soluble salt of terbium, a soluble salt of europium and a bismuth source as raw materials, and DMSO as the coordinating ions and solvent of europium and terbium, and synthesizes the perovskite-structured luminescent material by a cooling crystallization method. The process is simple, the raw materials are simple, the product purity is high, the production cycle is short, the reaction conditions are mild, the raw material price is relatively low, the economic benefit is high, it is easy to promote, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a single crystal structure diagram of the (Tb·8DMSO)BiCl6 crystal prepared in Example 1 of the present invention.
[0024] Figure 2 The (Tb·8DMSO)BiCl6, (Tb 0.8 Eu0.2 ·8DMSO)BiCl6、(Tb 0.6 Eu 0.4 ·8DMSO)BiCl6、(Tb 0.4 Eu 0.6 ·8DMSO)BiCl6、(Tb 0.2 Eu 0.8 ·8DMSO)BiCl6 and (Eu·8DMSO)BiCl6 crystals.
[0025] Figure 3 The fluorescence emission spectra of (Eu·8DMSO)BiCl6 crystals and the soluble europium salt EuCl3·6H2O prepared in Example 6 of the present invention.
[0026] Figure 4 The (Tb·8DMSO)BiCl6, (Tb 0.8 Eu 0.2 ·8DMSO)BiCl6、(Tb 0.6 Eu 0.4 ·8DMSO)BiCl6、(Tb 0.4 Eu 0.6 ·8DMSO)BiCl6、(Tb 0.2 Eu 0.8 Emission spectra of (Eu·8DMSO)BiCl6 and (Eu·8DMSO)BiCl6 crystals under 365nm excitation.
[0027] Figure 5 The (Tb·8DMSO)BiCl6, (Tb 0.8 Eu 0.2 ·8DMSO)BiCl6、(Tb 0.6 Eu 0.4 ·8DMSO)BiCl6、(Tb 0.4 Eu 0.6 ·8DMSO)BiCl6、(Tb 0.2 Eu 0.8 ·8DMSO)BiCl6 and (Eu·8DMSO)BiCl6 crystals; the asterisks S1-S6 in the figure correspond to the color coordinates of the crystals obtained in Examples 1-6, respectively.
[0028] Figure 6 The (Tb·8DMSO)BiCl6, (Tb0.8 Eu 0.2 ·8DMSO)BiCl6、(Tb 0.6 Eu 0.4 ·8DMSO)BiCl6、(Tb 0.4 Eu 0.6 ·8DMSO)BiCl6、(Tb 0.2 Eu 0.8 Actual pictures of (Eu·8DMSO)BiCl6 and (Eu·8DMSO)BiCl6 crystals under ultraviolet light with wavelengths of 365nm and 395nm. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific examples. The following examples are only used to introduce the present method and are not intended to limit the scope of implementation of the present invention.
[0030] The raw materials used in the following examples are all analytical grade reagents, and the glass bottles used are rinsed three times with alcohol and deionized water and then inverted to dry before use.
[0031] Example 1
[0032] Provided is a method for preparing a (Tb·8DMSO)BiCl6 lead-free perovskite crystal, comprising the following steps:
[0033] (1) Ensure that the glassware is clean before use. Add 0.5 mmol TbCl3·6H2O, 0.5 mmol SbCl3 and a cleaned magnet in a 20 ml glass bottle, then add 10 mL DMSO (dimethyl sulfoxide) in a fume hood, and then heat and stir in an oil bath. Control the temperature at about 90 °C and stir for about 1.5 h.
[0034] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0035] (3) After the cooling and crystallization is completed, the crystals are washed with isopropanol for 2-3 times, and then dried and collected to obtain (Tb·8DMSO)BiCl6 perovskite crystals.
[0036] Example 2
[0037] Provide a (Tb 0.8 Eu 0.2 ·8DMSO) BiCl6 lead-free perovskite crystal preparation method, comprising the following steps:
[0038] (1) Ensure that the glassware is clean before use. Add 0.4mmolTbCl3·6H2O, 0.1mmolEuCl3·6H2O, 0.5mmolSbCl3 and a cleaned magnet in a 20ml glass bottle, then add 10mL LDMSO in a fume hood, and heat and stir in an oil bath. Control the temperature at about 90℃ and stir for about 1.5h.
[0039] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0040] (3) After the cooling and crystallization is completed, the crystals are washed 2-3 times with isopropanol, and then dried and collected to obtain (Tb 0.8 Eu 0.2 ·8DMSO)BiCl6 perovskite crystals.
[0041] Example 3
[0042] Provide a (Tb 0.6 Eu 0.4 ·8DMSO) BiCl6 lead-free perovskite crystal preparation method, comprising the following steps:
[0043] (1) Ensure that the glassware is clean before use. Add 0.3mmolTbCl3·6H2O, 0.2mmolEuCl3·6H2O, 0.5mmolSbCl3 and a cleaned magnet in a 20ml glass bottle, then add 10mLDMSO in a fume hood, and then heat and stir in an oil bath. Control the temperature at about 90℃ and stir for about 1.5h.
[0044] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0045] (3) After the cooling and crystallization is completed, the crystals are washed 2-3 times with isopropanol, and then dried and collected to obtain (Tb 0.6 Eu 0.4 ·8DMSO)BiCl6 perovskite crystals.
[0046] Example 4
[0047] Provide a (Tb 0.4 Eu 0.6 ·8DMSO) BiCl6 lead-free perovskite crystal preparation method, comprising the following steps:
[0048] (1) Ensure that the glassware is clean before use. Add 0.2mmolTbCl3·6H2O, 0.3mmolEuCl3·6H2O, 0.5mmolSbCl3 and a cleaned magnet in a 20ml glass bottle, then add 10mLDMSO in a fume hood, and then heat and stir in an oil bath. Control the temperature at about 90℃ and stir for about 1.5h.
[0049] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0050] (3) After the cooling and crystallization is completed, the crystals are washed 2-3 times with isopropanol, and then dried and collected to obtain (Tb 0.4 Eu 0.6 ·8DMSO)BiCl6 perovskite crystals.
[0051] Example 5
[0052] Provide a (Tb 0.2 Eu 0.8 ·8DMSO) BiCl6 lead-free perovskite crystal preparation method, comprising the following steps:
[0053] (1) Ensure that the glassware is clean before use. Add 0.1mmol TbCl3·6H2O, 0.4mmol EuCl3·6H2O, 0.5mmol SbCl3 and a cleaned magnet in a 20ml glass bottle, then add 10mL DMSO in a fume hood, and then heat and stir in an oil bath. Control the temperature at around 90℃ and stir for about 1.5h.
[0054] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0055] (3) After the cooling and crystallization is completed, the crystals are washed 2-3 times with isopropanol, and then dried and collected to obtain (Tb 0.2 Eu 0.8 ·8DMSO)BiCl6 perovskite crystals.
[0056] Example 6
[0057] Provided is a method for preparing (Eu·8DMSO)BiCl6 crystals, comprising the following steps:
[0058] (1) Ensure that the glassware is clean before use. Add 0.5mmolEuCl3·6H2O, 0.5mmolSbCl3 and a cleaned magnet in a 20ml glass bottle, then add 10mLDMSO in a fume hood, and then heat and stir in an oil bath at about 90℃ for about 1.5h.
[0059] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0060] (3) After the cooling and crystallization is completed, the crystals are washed with isopropanol for 2-3 times, and then dried and collected to obtain (Eu·8DMSO)BiCl6 perovskite crystals.
[0061] Comparative Example 1: Solvent is DMF
[0062] (1) Ensure that the glassware is clean before use. Add 0.5 mmol EuCl3·6H2O, 0.5 mmol SbCl3 and a cleaned magnet in a 20 ml glass bottle, then add 10 mL DMF (N,N-dimethylformamide) in a fume hood, and then heat and stir in an oil bath at about 90 °C for about 1.5 h.
[0063] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0064] (3) After cooling, the glass bottle still contained a clear and transparent solution, and no crystals were obtained.
[0065] Comparative Example 2: Solvent is DMAC
[0066] (1) Ensure that the glassware is clean before use. Add 0.5 mmol EuCl3·6H2O, 0.5 mmol SbCl3 and a cleaned magnetic particle in a 20 ml glass bottle, then add 10 mL DMAC (N,N-dimethylacetamide) in a fume hood, and then heat and stir in an oil bath at about 90 °C for about 1.5 h.
[0067] (2) After the solution in the glass bottle becomes clear and transparent, seal the oil bath pot with plastic wrap and place it in a programmed cooling oven for cooling and crystallization. The cooling program is 3°C per hour for 24 hours.
[0068] (3) After cooling, the glass bottle still contained a clear and transparent solution, and no crystals were obtained.
[0069] Comparative Examples 1 and 2 show that stable zero-dimensional bismuth-based perovskite crystal materials can only be obtained in DMSO solvent, indicating that the ligand solvent is one of the key factors affecting the structural characteristics of rare earth ion composite materials.
[0070] Figure 1 The crystal structure of the zero-dimensional bismuth-based perovskite structure luminescent material (Tb·8DMSO) BiCl6 prepared in Example 1 belongs to the monoclinic system, the space group is P2 / c, and the unit cell parameters are α=90°,β=91.8°,γ=90°,unit cell volume like Figure 1 As shown in the crystal structure of (Tb·8DMSO)BiCl6, Bi 3+ With six Cl -1 Coordinate to form an octahedral structure, Tb 3+ It coordinates with eight DMSO molecules to form A-site ions, which separate the octahedrons to form a zero-dimensional perovskite-like structure.
[0071] Figure 2 The powder X-ray diffraction (XRD) data of Examples 1 to 6 show that the diffraction peak positions of the six crystals almost completely overlap, indicating that the change of Tb 3+ and Eu 3+ The ratio does not affect the crystal structure.
[0072] Figure 3 The fluorescence emission spectra of Example 1 and the rare earth salt of europium are shown. The absorption coefficient of the rare earth salt of europium in the visible light and ultraviolet spectrum regions is relatively small, while in the present invention, the organic ligand and the inorganic ligand significantly increase the fluorescence intensity of the rare earth ions.
[0073] Figure 4 and Figure 5 The fluorescence emission spectra and color coordinate diagrams of the crystalline materials prepared in Examples 1 to 6 are shown in Table 1. 3+ and Eu 3+ When the ratio is 1:0, the characteristic peak of the material is consistent with the fluorescence characteristic peak of terbium ions, and the luminescent color is green; 3+ and Eu 3+ As the ratio changes, the luminescent color also changes. When the ratio reaches 0:1, its characteristic peak is consistent with the fluorescence characteristic peak of europium ions, and the luminescent color is red.
[0074] Figure 6The actual pictures of the crystal materials prepared in Examples 1 to 6 under UV lamps with wavelengths of 365nm and 395nm, from left to right are the crystal materials obtained in Examples 1 to 6. We can observe that the luminescent colors of the materials under the two different wavelengths of UV lamps are obviously different, especially when Tb 3+ and Eu 3+ When the ratio is 4:1, 3:2, and 2:3, the difference is more significant.
[0075] The above examples are preferred experimental methods of the present invention and are not intended to limit the implementation methods. Obvious changes based on the present invention are still within the protection of the present invention.
Claims
1. A zero-dimensional bismuth-based perovskite structure luminescent material, characterized in that: The structural formula of the luminescent material is (Tb x Eu 1-x •8DMSO)BiX6, where 0≤x≤1, X is Cl - Br - ,I - One or more of; The preparation of the zero-dimensional bismuth-based perovskite structure light-emitting material comprises the following steps: 1) According to the calculated ratio of the structure, weigh the soluble salt of terbium, the soluble salt of europium and the bismuth source in sequence and add them to the dimethyl sulfoxide solution, then heat to 65-95° C. and stir for 0.5-2.5 hours; 2) After stirring the mixture in step 1) until it is clear and transparent, the temperature is lowered by 2-8°C per hour for 16-30 hours, and the mixture is cooled and crystallized. After post-treatment, a zero-dimensional bismuth-based perovskite structured luminescent material is obtained.
2. A method for preparing the zero-dimensional bismuth-based perovskite structure luminescent material according to claim 1, characterized in that: The following steps are involved: 1) According to the calculated ratio of the structure, weigh the soluble salt of terbium, the soluble salt of europium and the bismuth source in sequence and add them to the dimethyl sulfoxide solution, then heat to 65-95° C. and stir for 0.5-2.5 hours; 2) After stirring the mixture in step 1) until it is clear and transparent, the temperature is lowered by 2-8°C per hour for 16-30 hours, and the mixture is cooled and crystallized. After post-treatment, a zero-dimensional bismuth-based perovskite structured luminescent material is obtained.
3. The preparation method according to claim 2, characterized in that: In the step 1), the soluble salt of terbium is one or more of hydrochloride, nitrate, carbonate and acetate.
4. The preparation method according to claim 2, characterized in that: In the step 1), the soluble salt of europium is one or more of hydrochloride, nitrate, carbonate and acetate.
5. The preparation method according to claim 2, characterized in that: In the step 1), the bismuth source is one or more of bismuth chloride, bismuth bromide and bismuth iodide.
6. The preparation method according to claim 2, characterized in that: In the step 2), the post-treatment is as follows: filtering the crystals, washing them with isopropanol or anhydrous ethanol for 2-3 times, and drying them.
Citation Information
Patent Citations
Method for increasing fluorescence yield and stability of non-lead halogen perovskite material
CN108329912A